Elliptical BandPassThree Dimensional Frequency Selective Surface with Multiple Transmission Zeros - Bimal Raj Dutta; Binod Kumar Kanaujia; Chhaya Dalela (Institute of Advanced Engineering and Science, 2018)
An elliptic band pass response three-dimensional Frequency Selective Surface (3D FSS) is designed from a single unit cell of 2D array of two shielded microstrip lines. The designed FSS provides pseudo-elliptic band-pass frequency response (5.4 – 9.6) GHz with its application in long-distance radio telecommunications and space communications etc. The four transmission zeros at 5.4GHz, 9.6GHz, 12.4GHz and 15GHz provides wide out-of-band frequency rejection. The 3D FSS is independent of the variations in the incident angle of the plane wave up to 60 degree. Each unit cell is a combination of two shielded microstrip lines with one having an air gap and the other one having in between rectangular metallic plate. When a TE polarized plane wave incidents perpendicular to the perfect electric conductor (PEC) boundary walls shielded microstrip lines, it results in two quasi-TEM modes namely air and substrate mode. The 3D FSS consists of multiple resonators with a multimode cavity having number of propagating modes. These resonating modes in phase provide transmission poles and when out of phase give transmission zeros. The 3D FSS structure is simulated using Ansys HFSS software with improved performance over 2DFSS, for many practical applications such as antenna sub-reflector, radomes and spatial filters.